Necesidad de reformar el art. 640 del código orgánico integral penal al ser improcedente por la falta de acusación fiscal - Paredes Criollo, Patricia Elizabeth (2015)
The new Code of Criminal Integral, Ecuadorian legislation introduced in countless new legal concepts in this field of law, are some really innovative and important for the speed and agility in the criminal proceedings are heard in the various Prosecutors and courts, country, as far as my research goal is concerned, I will delve critical study of what concerns the direct method applicable in flagrante delicto. In Ecuador for several years now, we have implemented the adversarial system, and is therefore that Article 195 of the Constitution of the Republic provides that the Attorney conduct the criminal investigation and preprocess proceedings.; who find merit accuse the alleged offenders before the competent court, meanwhile Comprehensive Organic Penal Code states that if no indictment is no judgment; It is for this reason that the prosecutor to hold public action, and operative objective, to count on sufficient evidence formulated in the evaluation stage and preparatory trial his accusation that as it says in the law this must meet several requirements, in constitutes a procedural solemnity without which it would violate the basic rules of due process because judges would attributing functions not compel. While the direct process concentrates all stages of the trial in one, from rating the flagrancia to direct trial hearing without leave room for there the pronouncement of the Prosecutor and the possibility that the defendant disagrees with that decision and the lack of opportunity to deny due process to make submissions on a procedural defects, prejudicialidad, procedure and jurisdiction parties and legitimacy of evidence, degrade the constitutional principle to the defense of the accused. Therefore the direct process becomes a process unconstitutional and violates several constitutional and legal principles that constrain the implementation and development of them becoming irrelevant. We briefly exposed reveals that the application of this procedure generates clearly legal uncertainty, which shows the legal issue raised for research, since the court comply with a provision adopted and enforced by the legislature, but without taking into account the legal consequences that this generates to punish with all the speed of a mild case of less serious crimes than others such as those involving a sentence of less freedom to five years, compared to offenses punishable by appropriate penalties are even exceeding 40 years of imprisonment, which is disproportionate, illegal and unjust in the eyes of society